Dry Sliding Friction and Wear Studies of Fly Ash Reinforced AA-6351 Metal Matrix Composites. (21st January 2013) - Uthayakumar, M.; Kumaran, S. Thirumalai; Aravindan, S.
Abstract : Fly ash particles are potentially used in metal matrix composites due to their low cost, low density, and availability in large quantities as waste by-products in thermal power plants. This study describes multifactor-based experiments that were applied to research and investigation on dry sliding wear system of stir-cast aluminum alloy 6351 with 5, 10, and 15 wt.% fly ash reinforced metal matrix composites (MMCs). The effects of parameters such as load, sliding speed, and percentage of fly ash on the sliding wear, specific wear rate, and friction coefficient were analyzed using Grey relational analysis on a pin-on-disc machine. Analysis of variance (ANOVA) was also employed to investigate which design parameters significantly affect the wear behavior of the composite. The results showed that the applied load exerted the greatest effect on the dry sliding wear followed by the sliding velocity.